Re-Thinking Firm Level Data Collection during COVID-19 : Using Mobile Sensing to Understand the Financial Behaviors of Entrepreneurs - Alibhai, Salman; Buehren, Niklas; Cucagna, Maria Emilia (World Bank, Washington, DC, 2020)
SMEs around the world are entering a crisis period in light of COVID-19, adding new urgency to understanding firm-level financial behaviors and challenges. At the same time, traditional methods of in-person data collection pose a health risk to both enumerator and firm and contravene social distancing guidelines and public health policies. Remote data collection methods such as phone sensing offer a viable and promising alternative. Phone sensing utilizes data generated from mobile phone usage, from GPS location to call logs to battery life – to offer insights on firm behavior, trends, and challenges. While the technology is still new and untested, this note explores some of the early insights gained from a pilot of mobile sensing technology to understand the financial behavior of women entrepreneurs in Ethiopia. Phone sensing data allows us to glean some insights into the lives and behaviors of entrepreneurs which traditional data collection might not reveal. One of the key finding of this pilot is that mobile phone sensing data correlates with business outcomes. Insights such as the ones from this pilot, if collected at a larger and more systematic scale, could enhance our understanding of borrower behavior, and could help lenders and policymakers better target potential borrowers, better understand when borrowers are likely to face adversity, and better design products to meet their needs.